Self-esteem assessment of high-risk pregnant women hospitalized in a public maternity (Research, Society and Development, 2023)
Objective: to evaluate the level of self-esteem of high-risk pregnant women hospitalized in a public maternity hospital, describing them in terms of their socio-personal and obstetric characteristics, in addition to pointing out a possible correlation of these characteristics with the level of self-esteem. Methodology: this is a descriptive, cross-sectional study with a quantitative approach that was carried out with 30 high-risk pregnant women hospitalized in a public maternity hospital of high complexity. For data collection, a socio-personal and obstetric characterization questionnaire was used. Self-esteem was assessed using the Rosenberg Self-Esteem Scale. The collected data were analyzed using the IBM Statistical Package for the Social Sciences version 20.0. The significance level adopted was p